2009
DOI: 10.3406/caf.2009.2424
|View full text |Cite
|
Sign up to set email alerts
|

Les femmes dans les parentèles contemporaines : atouts et contraintes d’une position centrale

Abstract: Sur les plans matériel, affectif et symbolique, l’implication des femmes dans la parentèle est supérieure à celle des hommes. Cette « centralité féminine » – qui se manifeste sous des formes variées dans les trois cercles concentriques de la parentèle et crée dans les relations du couple avec cette dernière un biais matrilatéral – se maintient malgré les transformations récentes de la famille. La conjonction des deux hypothèses du « matricentrage » et du « gynécentrage » permet de l’interpréter comme un « inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
2
4
0
3
Order By: Relevance
“…This security appears to be assured for some men through partnership whereas children and parentsthe lineageappear more as the basis of solidarity for women. This confirms the matrifocal orientation of French kinship networks regarding contacts and services (Déchaux 2009). The effects of parent's gender on housing solidarities are coherent with existing research that revealed more service exchanges (Chan 2008;Silverstein and Bengtson 1997) as well as closer relationships of adult children with their mothers (Silverstein and Bengtson 1997).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This security appears to be assured for some men through partnership whereas children and parentsthe lineageappear more as the basis of solidarity for women. This confirms the matrifocal orientation of French kinship networks regarding contacts and services (Déchaux 2009). The effects of parent's gender on housing solidarities are coherent with existing research that revealed more service exchanges (Chan 2008;Silverstein and Bengtson 1997) as well as closer relationships of adult children with their mothers (Silverstein and Bengtson 1997).…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, middle-aged men, living alone but locked-down with a kin, were more likely to join a partner than women: 67% of men over 40 against 9% of women living alone but shutdown with a housemate. These findings confirm the central position of women in vertical kinship solidarities (Déchaux 2009;Silverstein and Bengtson 1997). They also confirm that middleaged men are more likely to rely on their partner than women (Costemalle, 2015).…”
Section: Free To Move? Inequalities In Facing the Lockdown With One'ssupporting
confidence: 69%
See 2 more Smart Citations
“…L'obligation alimentaire apportée aux personnes âgées vivant à domicile est d'autant plus assumée par la famille que les bénéficiaires appartiennent aux catégories modestes ; dans les classes supérieures, en revanche, l'aide professionnelle est beaucoup plus présente (Dutheil, 2001 (Desjeux et al, 1998, p. 63 Pour résumer la manière dont se mobilisent les apparentés de M. Blinet, on peut parler de « cercles » de mobilisation concentriques, reprenant ainsi une image déjà développée concernant les personnes mobilisables par ego au sein de sa parentèle, entendue comme réseau de relations affinitaires au sein de la parenté (Déchaux, 2009…”
Section: Les éTablissements Pour Personnes âGées En Franceunclassified